2007
DOI: 10.1002/ajh.20856
|View full text |Cite
|
Sign up to set email alerts
|

Primary adrenal adult T‐cell leukemia/lymphoma: A case report and review of the literature

Abstract: Primary adrenal lymphoma (PAL) is very rare; the majority of cases reported previously were of B‐cell origin. We report a rare case of primary adrenal adult T‐cell leukemia/lymphoma (primary adrenal ATLL). ATLL is a highly aggressive T‐cell type non‐Hodgkin's lymphoma and etiologically associated with human T‐cell lymphotropic virus 1 (HTLV‐1). Most ATLL patients present with leukemia and widespread lymphadenopathy. A 37‐year‐old Japanese woman presented with back pain in January 2004. Examination showed no pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Bilateral involvement is seen in 50% of patients [23], and bilateral involvement of the adrenal gland is considered as a single-site extranodal involvement [24]. In the present study, bilateral lesions were seen in 6 patients.…”
Section: Resultsmentioning
confidence: 46%
“…Bilateral involvement is seen in 50% of patients [23], and bilateral involvement of the adrenal gland is considered as a single-site extranodal involvement [24]. In the present study, bilateral lesions were seen in 6 patients.…”
Section: Resultsmentioning
confidence: 46%
“…Differential diagnoses include cortical adenoma, pheochromocytoma, metastatic-disease, and adrenocorticotropic hormone (ACTH) dependent Cushing’s syndrome [12, 13]. The definitive diagnosis of primary adrenal lymphoma is made by an image-guided percutaneous biopsy, surgical exploration, or a postmortem examination [1, 2, 14]. Histopathologically, the most common type of primary adrenal lymphoma is B-cell type, mainly diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…DLBCL is the most common type of PAL (70%), followed by mixed large and small cell, small noncleaved cell, and the undifferentiated type. On immunostaining, the majority of this entity is seen to have originated from B cells [8,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…This decision was based on the results of study LNH87-2 of the Adult Lymphoma Study Group (French: Groupe d’Etudes des Lymphomes de l’Adulte) before the rituximab era [12]. In the literature, about 70 cases were published with rare complete or partial responses, with an overall survival of 4 months [10,11,12,13]. Kim et al reported recent data about 14 PAL patients treated with an R-CHOP regimen.…”
Section: Discussionmentioning
confidence: 99%